Content analysis of agricultural news with and without photographs in selected Nigerian Daily Newspapers - Olajide, B. R.; Fawole, O. P. (The Nigerian Journal of Rural Extension and Development, 2023)
Photographs have the potency to enhance farmers’ understanding of news items in the print media. This, therefore, presupposes that news items on innovations in agriculture should be representative and strategically placed in the newspapers. Past studies have focused on coverage of agricultural news with little attention to whether such stories were accompanied by photographs that tell the story. This study therefore focused on content analysis of agricultural columns with and without photographs in selected Nigerian Daily Newspapers. Two Nigeria’s newspapers (New Nigeria and the Guardian) were purposively selected based on geographical location, large circulation, prominence and blend of agricultural news and activities. A total of 144 news items with and without photographs were analysed using frequency and percentages for frequency, space allotment, prominence and representativeness of the photographs. Results show that most of the stories (90.3%) were accompanied with photographs with the Guardian allotting more space to photographs in general (7,902.75sqcm) compared to New Nigeria (4,190.33sqcm). However, while the Guardian had more space for agricultural produce and products (6,094.34sqcm) compared to New Nigeria’s 2,143.52sqcm, New Nigeria had more space (1,092.72sqcm) for agricultural equipment than the Guardian’s 820.58sqcm. Most of the photographs (62.5%) were not representative of the story lines and none was strategically placed (100.0%) in the Newspapers. It is recommended that editors should ensure that photographs for agricultural news items are representative of the content of the story lines as well as placed in strategic location as space allows in their newspapers.